Pottery and Jewish Settlement in Late Roman Galilee - Magness, Jodi (Bulletin of ASOR, 2015)
In this article, we consider a recent proposal that Jewish settlement in eastern Galilee experienced a demographic crisis in the late third century and first half of the fourth century C.E. This proposal is based largely on pottery that was collected during intensive surveys of sites in eastern lower Galilee, supplemented by limited data from excavations. However, the ambiguous nature of the survey data means that this material can be interpreted to support a different settlement picture. The crux of our disagreement hinges on the dating and interpretation of the ceramic evidence and the use of survey data as a basis for sweeping historical reconstructions. To demonstrate these points, we discuss three sites that were surveyed (Nasr ed-Din, Parod, and Horvat Ammudim) and analyze selected deposits from the excavations at Capernaum and Meiron. We conclude that the data from these sites can be interpreted as supporting a picture of continuous settlement through the fourth, fifih, and sixth centuries, even allowing for fluctuations in distribution, intensity, and size.